2006
DOI: 10.1089/scd.2006.15.381
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein Regulates Differentiation of Human Neural Stem Cells

Abstract: Although amyloid beta (Abeta) deposition has been a hallmark of Alzheimer's disease (AD), the absence of a phenotype in the beta amyloid precursor protein (APP) knockout mouse, tends to detract our attention away from the physiological functions of APP. Although much attention has been focused on the neurotoxicity of Abeta, many studies suggest the involvement of APP in neuroplasticity. We found that secreted amyloid precursor protein (sAPP) increased the differentiation of human neural stem cells (hNSCs) in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 41 publications
2
51
1
1
Order By: Relevance
“…In a recent study, we demonstrated that treatment with recombinant sAPP promoted migration and differentiation of HNSCs in culture, and 22C11 antibodymediated neutralization of sAPP in media inhibited these effects dose dependently (15). We also reported that HNSCs transplanted into APP knockout mice showed less migration and differentiation compared with wild-type mice (15). On the basis of these observations, we suggest that APP may be acting as a signaling factor in migration and differentiation of HNSCs.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a recent study, we demonstrated that treatment with recombinant sAPP promoted migration and differentiation of HNSCs in culture, and 22C11 antibodymediated neutralization of sAPP in media inhibited these effects dose dependently (15). We also reported that HNSCs transplanted into APP knockout mice showed less migration and differentiation compared with wild-type mice (15). On the basis of these observations, we suggest that APP may be acting as a signaling factor in migration and differentiation of HNSCs.…”
Section: Discussionmentioning
confidence: 60%
“…Both of these events involve migration and differentiation of NSCs, suggesting that APP may also play an important physiological function in regulating stem cell biology. In a recent study, we demonstrated that treatment with recombinant sAPP promoted migration and differentiation of HNSCs in culture, and 22C11 antibodymediated neutralization of sAPP in media inhibited these effects dose dependently (15). We also reported that HNSCs transplanted into APP knockout mice showed less migration and differentiation compared with wild-type mice (15).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A large number of studies have suggested that sAPP␣ has trophic properties on neural stem cells (9,27,28,37,38). In our studies, recombinant human sAPP␣ had no effect on proliferation, nor did immunoprecipitation of endogenous secreted mouse sAPP␣ inhibit proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that human NPCs exposed to high concentrations of secreted APP differentiated into astrocytes rather than into neurons. In vivo, human NPCs transplanted into the brain of APP transgenic mice preferentially differentiated into glia (Kwak et al, 2006), indicating that under physiological conditions APP plays a role in neural stem biology, probably by inducing STAT3 phosphorylation and JAK1 gene expression (Sugaya, 2008). APP was also shown to increase generation of Notch intracellular domain and expression of Hes1, a mechanism which may work in concert with the JAK/STAT pathway to push differentiation of human NPCs toward glia (Sugaya, 2008).…”
Section: Review Of He and Shenmentioning
confidence: 99%